2020
DOI: 10.1080/1828051x.2020.1722970
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance, egg-related indices, blood profiles, and interferon-Ɣ gene expression of laying Japanese quails fed on Tenebrio molitor larva meal as a replacement for fish meal

Abstract: The present experiment was conducted to investigate effects of Tenebrio molitor (TM) as a replacement for fish meal on egg productive and qualitative traits, serum biochemical parameters, haematology and interferon-Ç gene expression in laying quails. A total of 250 laying Japanese quails (Coturnix japonica), at 74 days of age were randomly allotted to five dietary treatments in a completely randomised design during a five-week period. Experimental treatments consisted of a basal diet (CTL) or basal diet supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…To our knowledge, there are very few studies about the use of insect meals in laying quails and they are divided among local insect species ( Das and Mandal, 2014 ), black soldier fly ( Dalle Zotte et al, 2019 ), and T. molitor ( Shariat Zadeh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, there are very few studies about the use of insect meals in laying quails and they are divided among local insect species ( Das and Mandal, 2014 ), black soldier fly ( Dalle Zotte et al, 2019 ), and T. molitor ( Shariat Zadeh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EU Regulation 2017/893 admitted the use of Tenebrio molitor ( TM ), however, to date, only the aquaculture sector can benefit of insects as ingredient for feed. However, very few studies specifically considered the use of insect meals in laying quails and they are divided into black soldier fly ( Dalle Zotte et al, 2019 ), T. molitor ( Shariat Zadeh et al, 2020 ) or other local insect species ( Das and Mandal, 2014 ). The preliminary evaluation of Shariat Zadeh et al (2020) found a positive correlation between the inclusion of TM larvae meal, the egg productive performance and the egg-related indices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The larvae of T. molitor (AKA yellow mealworm) are a common protein source for livestock and pets because they are easy to breed, high in protein, and have a high rate of assimilation of nitrogen from their feed (11)(12)(13)(14). The yellow mealworm is not only a good source of protein, for instance, the effect of feeding yellow mealworms to chickens and fish as a protein supplement for herbivores (15)(16)(17)(18), but also beneficial for improving the utilization rate of the intestinal protein of livestock, promoting their growth, increasing yield, and optimizing quality (19).…”
Section: Introductionmentioning
confidence: 99%